ONTOLOGICAL METAPHOR CONCEPTUALIZING “BAD THINGS” IN ENGLISH AND VIETNAMESE POLITICAL DISCOURSE (Journal of Foreign Language Studies, 2020)
Political discourses serve as an instrument for politicians and political organizations to pursue and execute power; and a frequently used linguistic device that political speakers opt to is metaphor. The article uses the semantic analysis method in line with theoretical frameworks of cognitive linguistics to depict and analyse ontological metaphors to conceptualize “bad things” as enemies or wounds/diseases in English and Vietnamese political discourses of some American and Vietnamese political leaders.
Keywords: Cognitive linguistics; conceptual metaphor; ontological metaphor; political discourse; bad thing; enemy; wound; disease